Evaluasi Kirkpatrick Level 3 terhadap Pelatihan on Job Development: (Studi Literatur) - As’syam. N. A; Hasyim. M. S; Hartanto Hartanto (Jurnal Pengembangan Ketenagakerjaan, 2025)
This study aims to evaluate the effectiveness of On-Job Development (OJD) training program for new employees at PT Nusa Toyotetsu using a qualitative descriptive approach. Data were collected through in-depth interviews, direct observation by supervisors, and self-assessment from training participants. The study highlights behavioral changes observed after the training, including improvements in discipline, compliance with standard operating procedures (SOP), use of personal protective equipment (PPE), teamwork, and independence. The findings indicate that the OJD training positively influenced employee behavior. However, the evaluation proces sstill faces challenges, such as the absence of standardized behavioral indicators and limited observation time. These results underline the importance of establishing a structured behavioral evaluation system as part of a long-term human resource development strategy within the company.